How science creates impact: A comment. Issue 1 (9th May 2022) - Willner, Arik
Abstract: Addressing the grand societal challenges is a task for science. To get this done, innovation needs to be the focus of all research institutions together with industry, as discussed in the following comment by Dr. Arik Willner. Abstract : Addressing the grand societal challenges is a task for science. To get this done innovation needs to be the focus of all research institutions together with industry, as discussed in the following comment by Dr. Arik Willner.